Revitalization of Tarompa Datuak Crafts Through Design Development as an Efforts to Strengthen Creative Economic Existence in the Era of Disruption - Amrizal Amri Muchtar; Ahmad Akmal; Purwo Prihatim; Sumadi Sumadi (Indonesian Journal of Economics, Social, and Humanities, 2020)
The tarompa datuak traditional craft is one of the Minangkabau ethnic local cultural assets which can be explored to strengthen the existence of a creative economy in West Sumatra. However, the development of this craft has been eroded by time, its products are less in demand by consumers, crafters are increasingly reduced and there is no regeneration, this is caused by the absence of innovation on the product, so that the ergonomic aspects and aesthetic have not become the standard of product feasibility by the crafters. Revitalizing the tarompa datuak through the development of its product design is an urgent step to take. It aims to enrich the variety of products, increase the welfare of the community and is part of cultural preservation. Revitalization is done by using research and development methods, which starts with exploring the tarompa datuak model that already exists in West Sumatra to become a trendy model, according to the needs and desires of consumers. The revitalization process begins with exploration, design, prototype, implementation and evaluation of product feasibility, so that the product developed is empirically tested. The success of this revitalization lies in the flexibility of the community in adapting to changes in the era of disruption. The results obtained: innovative products, cultural pelestraian and community economic empowerment.